Red Sea Suberea mollis Sponge Extract Protects against CCl4-Induced Acute Liver Injury in Rats via an Antioxidant Mechanism. (19th August 2014) - Abbas, Aymn T.; El-Shitany, Nagla A.; Shaala, Lamiaa A.; Ali, Soad S.; Azhar, Esam I.; Abdel-dayem, Umama A.; Youssef, Diaa T. A.
Abstract : Recent studies have demonstrated that marine sponges and their active constituents exhibited several potential medical applications. This study aimed to evaluate the possible hepatoprotective role as well as the antioxidant effect of the Red Sea Suberea mollis sponge extract (SMSE) on carbon tetrachloride- (CCl4 -) induced acute liver injury in rats. In vitro antioxidant activity of SMSE was evaluated by 2, 2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) assay. Rats were orally administered three different concentrations (100, 200, and 400 mg/kg) of SMSE and silymarin (100 mg/kg) along with CCl4 (1 mL/kg, i.p., every 72 hr) for 14 days. Plasma aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and total bilirubin were measured. Hepatic malondialdehyde (MDA), reduced glutathione (GSH), nitric oxide (NO), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) were also measured. Liver specimens were histopathologically examined. SMSE showed strong scavenging activity against free radicals in DPPH assay. SMSE significantly reduced liver enzyme activities. Moreover, SMSE significantly reduced hepatic MDA formation. In addition, SMSE restored GSH, NO, SOD, GPx, and CAT. The histopathological results confirmed these findings. The results of this study suggested a potent protective effect of the SMSE against CCl4 -induced hepatic injury. This may be due to its antioxidant and radical scavenging activity.